Stop and think learning : teacher's guide for motivating children : including those with special needs - Petersen, Lindy (Camberwell, Vic. : Australian Council for Educational Research, 1995)
The classroom cocktail. Motivating learning: the ingredients and recipe. Proactive plans: following the recipe. Personal taste: my views on some special needs. Learning and relating: the good mixers.
Keywords: Education; Learning, Psychology of; Motivation in education; Learning disabled children -- Education; Underachievers -- Education; Social skills in children -- Study and teaching